Beware of Stereotypes: Are Classmates' Stereotypes Associated With Students' Reading Outcomes?. Issue 1 (25th February 2020) - Muntoni, Francesca; Wagner, Jenny; Retelsdorf, Jan
Abstract : This study examined the associations between classmates' reading‐related gender stereotypes and students' reading self‐efficacy, self‐concept, motivation, and achievement. Our sample consisted of 1, 508 fifth‐grade students (49% girls; age: 10.89 years); data were collected at two time points. Multilevel analyses yielded two main results: First, there was a relation between students' individual reading‐related gender stereotypes and their reading self‐concept, self‐efficacy, and motivation with boys experiencing negative and girls experiencing positive effects. Second, a contextual effect was found: after controlling for students' individual reading‐related gender stereotypes, classmates' gender stereotypes were negatively related to all of the boys' reading outcomes. The results provide evidence for the assumption that classmates are important communicators of gender stereotypes and that they reinforce conforming behaviors.